Analysis of Company Cost Work on Disclosure of Company Environment Responsibility (An Empirical Study on the Implementation of Regulation of Go Public Companies in Indonesia) - Susenohaji MM (Jurnal VOK@SINDO, 2014)
the social and environment responsibilities of the companies in Indonesia , based on Law of Re public of Indonesia Number 40 of 2007 and Government Rule Number 47 of 2012, becomes significant variable on the difference of financial work in Indonesia. Population of the study is divided into two types of companies (high profile and low profile) that will be used for moderator variable to investigate society reaction on social responsibility of companies. In order to highlight that particular influence, this study involves high profile and low profile companies to measure society reaction. Purposive sampling is employed by involving two kinds of data based on the year, 2005-2006 (2 years before the implementation of the Law) and 2009-2010 (2 years after the implementation of the Law). The result shows that disclosure of social and environment costs do not influence financial work of the companies significantly. This finding strengthens the previous studies in Indonesia (Utomo, 2000; Rasmiati, 2001; Yuningsih, 2003). This means that companies’ awareness in Indonesia on environment responsibility is still low and society have not involved variables of social and environment responsibilities of companies as determining factors in investment decision-making (Sudibyo, 1998).